2023
DOI: 10.3389/fpsyg.2023.1092725
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial predictors in upper-extremity vascularized composite allotransplantation: A qualitative study of multidimensional experiences including patients, healthcare professionals, and close relatives

Abstract: BackgroundThe impact of patient-specific psychosocial factors on functional outcomes after upper-extremity (UE) vascularized composite allotransplantation (VCA) is poorly understood. The objective of this study was to identify relevant psychosocial predictors for success or failure of UE VCA in an Austrian cohort.MethodsA qualitative study was undertaken consisting of semi-structured interviews with UE VCA staff, transplanted patients, and close relatives. Participants were asked about their perceptions of fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Unsurprisingly, the need for expert interdisciplinary collaboration permeates into the psychosocial domain as well. Hummel et al conducted semi-structured interviews among UE staff, transplant patients, and relatives and determined that interdisciplinary teams with adequate resources for patient selection as well as ongoing close provider involvement contribute to transplantation success ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unsurprisingly, the need for expert interdisciplinary collaboration permeates into the psychosocial domain as well. Hummel et al conducted semi-structured interviews among UE staff, transplant patients, and relatives and determined that interdisciplinary teams with adequate resources for patient selection as well as ongoing close provider involvement contribute to transplantation success ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, social work departments play a vital role in ensuring that a robust social support system is in place as patients work to regain a sense of self, body image, and identity ( 9 , 12 , 30 32 ). In particular, patients and their caregivers have identified community and caregiver support as crucial factors in VCA success ( 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…8 In addition, consistent with our study, other research on UE VCA providers and recipients found that adherence to the transplant protocol and self-motivation during rehabilitation is essential to patient selection and pivotal to the success of hand transplantation. 24 A key finding was the importance participants placed on a "good social support system" in determining a patient's suitability for UE VCA. Other research with UE VCA recipients similarly identified the importance of a quality support system as recipients recounted the practical and emotional support provided to them by their networks.…”
Section: Discussionmentioning
confidence: 99%
“… 8 In addition, consistent with our study, other research on UE VCA providers and recipients found that adherence to the transplant protocol and self-motivation during rehabilitation is essential to patient selection and pivotal to the success of hand transplantation. 24 …”
Section: Discussionmentioning
confidence: 99%
“…After all, rapport between patients and their healthcare team have demonstrated improved patient outcomes. 36 If a loved one is verbally communicating on the patient’s behalf during the appointment, still addressing the patient first and foremost and understanding how the patient communicates their agreement or disagreement to what is being said will allow for the active involvement of the patient whose care is being discussed.…”
Section: Tic In Vcamentioning
confidence: 99%